Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1016/0735-1097(95)00460-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of coronary calcification and angiographic stenoses in patients undergoing coronary angiography

Abstract: Electron beam computed tomographic calcium scores correlate moderately well with angiographic findings. These scores predict coronary heart disease-related events in patients undergoing angiography as well as do the number of angiographically affected arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
192
1
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(205 citation statements)
references
References 27 publications
5
192
1
7
Order By: Relevance
“…Several other studies, including a study in young adults, 34 have found relationships between EBCT-measured coronary calcium and coronary risk factors. 34 -36 Coronary calcium has also been found to predict mortality 37 and CHD events. [37][38][39] These findings confirm that coronary calcium is a marker of atherosclerosis and suggest that it is a useful tool in studying the origins of atherosclerotic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies, including a study in young adults, 34 have found relationships between EBCT-measured coronary calcium and coronary risk factors. 34 -36 Coronary calcium has also been found to predict mortality 37 and CHD events. [37][38][39] These findings confirm that coronary calcium is a marker of atherosclerosis and suggest that it is a useful tool in studying the origins of atherosclerotic heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of calcification as measured by EBT can also predict silent myocardial infarction (20). Even in asymptomatic patients, coronary calcification is a strong predictor of cardiovascular morbidity and mortality (24). Thus, the hemodynamic and functional changes associated with vascular calcification and remodeling have real and significant clinical impact that can affect morbidity and mortality among dialysis patients.…”
Section: Clinical Impact Of Calcificationmentioning
confidence: 99%
“…Both decreasing DBP (the principal moving force for coronary perfusion) (25) and increasing PP (26) are associated with poor survival in hemodialysis patients (24). However, high postdialysis DBP of 90 mmHg or greater has also been associated with increased cardiovascular mortality (27).…”
Section: Clinical Impact Of Calcificationmentioning
confidence: 99%
“…9 Four large studies have been published regarding cardiac prognosis and EBCT calcium score. Detrano and colleagues 15 examined the relative prognostic value of coronary calcium for predicting coronary heart diseaserelated events in 491 patients (mean age, 55±12 years) referred for angiography who also underwent EBCT scanning. Thirteen documented coronary heart disease-related deaths (sudden cardiac death in 12 and a fatal infarction in 1) and 8 nonfatal myocardial infarctions occurred, with an 86% complete follow-up during a period of 30±13 months.…”
Section: Coronary Calcium As a Prognostic Indicatormentioning
confidence: 99%
“…[15][16][17][18] The National Heart, Lung, and Blood Institute (NHLBI) recently put forward an RFP (request for proposals) using EBCT, among other noninvasive methods, to study subclinical cardiovascular disease (RFP-…”
mentioning
confidence: 99%